Effects of sodium tripolyphosphate on the rheological properties of concrete: Mechanical, microstructural and carbon footprint - André Pico-Molineros; Natividad García-Troncoso; Jorge Flores-Rada; Dan V. Bompa (Results in Engineering)
Chemical additives used in concrete production are significant contributors to environmental pollution, as many are derived from petrochemical sources or require energy-intensive processes that increase CO2 emissions. This study investigates the effects of Sodium Tripolyphosphate (STPP) as a sustainable chemical additive by analyzing rheological, mechanical, and microstructural properties of concrete made with High Early Strength (HE) cement, focusing on workability, compressive strength, setting time, and carbon footprint. Testing was conducted in accordance with international and national standards, including slump, compressive strength, air content, setting time, scanning electron microscopy (SEM), thermogravimetric analysis (TGA), and embodied carbon assessment. Five concrete mixes with varying STPP dosages (0 %, 2.5 %, 5 %, 7.5 %, and 10 % relative to cement weight) were tested in both fresh and hardened states. Results demonstrated that STPP enhances workability and early compressive strength while reducing carbon footprint. Specifically, dosages of 2.5 % and 5 % yielded the best performance, achieving significant increases in early compressive strength and a reduction in carbon footprint by 11.2 % compared to conventional concrete. However, higher STPP dosages (>7.5 %) delayed setting times by more than one day and promoted excessive ettringite formation, leading to microcracking and reduced long-term strength. These findings highlight that incorporating STPP at optimized dosages (<5 %) improves the sustainability and performance of HES cement concrete, offering a viable alternative to conventional chemical additives in alignment with sustainable construction practices.